Highly Conductive Alkaline‐Earth Metal Electrodes: The Possibility of Maintaining Both Low Work Function and Surface Stability for Organic Electronics. Issue 15 (14th May 2020) - Liu, Yunfei; Ding, Tao; Chen, Xiaotian; Bai, Fuquan; Genco, Armando; Wang, Haoran; Chen, Chen; Chen, Ping; Mazzeo, Marco; Zhang, Yuantao; Duan, Yu
Abstract: The realization of a highly efficient and transparent light‐emitting display isan ambitious but highly desirable goal since several obstacles need to be solved. One of the most challenging issues is the fabrication of a suitable transparent cathode on the top emitting surface. Evaporated Ca thin film is one theoretically promising candidate due to its remarkable optical transparency, conductivity, and matched work function (WF) on the electron injection side. However, until now, keeping metallic Ca working as a stand‐alone electrode is not possible because its highly reactive characteristics cause ultrathin Ca film to react with organics. In this work, atomic layer deposition ZnO is presented with the intention of protecting a vulnerable ultrathin Ca layer while preserving its low WF in the entire structure. In this research, a transparent cathode that maintains a low WF of 3.31 eV is built, enabling highly transparent (nearly 90% in the visible range) organic light‐emitting diodes with external quantum efficiencies that reach 22.7%, 19.3%, and 17.9% for green, yellow, and blue emissions, respectively, and reaching an emission balance. The luminance of the devices is about three times higher when compared with the devices without protective structures, which are even likely to fail to operate. Abstract : Vulnerable materials such as alkaline‐earth metals show promising characteristics for optoelectronics. However, they are also extremely reactive when in contact with other materials. In this research, a strategy for protecting alkaline‐earth metal from a reactive organic interface is proposed. Moreover, the strategy maintains the transparency and conductivity, and most importantly, low work function, enabling highly efficient transparent organic light‐emitting diodes.